The Validity of Electronic Evidence and Its Relation to Personal Data Protection - Manurung, Karina Hasiyanni; Harefa, Beniharmoni (Jurnal Daulat Hukum, 2024)
An examination of electronic evidence within the context of Indonesian criminal law focuses on the evolving role of electronic evidence in criminal proceedings, highlighting the challenges arising from the absence of clear regulation in the Indonesian Criminal Procedure Code (KUHAP) and the necessity of balancing this with privacy rights under the Personal Data Protection Law (UU PDP). Electronic evidence, such as digital data and electronic documents, is increasingly recognized under the applicable laws in Indonesia, yet its practical application remains complex within the criminal justice system.  This research employs a normative legal methodology, analyzing relevant legal provisions and their interplay, particularly concerning the validity of electronic evidence and data privacy. Both statutory and conceptual approaches are utilized, reviewing primary legal materials such as KUHAP, UU PDP, and related regulations. The study also examines key legal principles, including compliance, transparency, and proportionality, in the context of handling electronic evidence.  Secondary data is gathered through a comprehensive literature review, including legal texts, academic books, and journals. The findings indicate significant gaps in the current legal framework, particularly regarding the procedural norms for evidence collection and the tension between privacy rights and criminal justice needs. The research concludes with recommendations for legal reforms aimed at integrating electronic evidence more effectively into KUHAP, ensuring greater consistency, safeguarding privacy, and promoting procedural fairness in criminal proceedings.